Family Court: its legal positions in Malaysia, Singapore and Australia / Nadia Edlina Zulkifli, Nor Ashikin Kamal and Wan Nurul Eliana Haslee Sharil - Zulkifli, Nadia Edlina; Kamal, Nor Ashikin; Haslee Sharil, Wan Nurul Eliana (2012)
Family Court; Its Legal Positions in Malaysia, Singapore and Australia is a research paper, which focuses on the position of a family court in Malaysia. This research paper examines on the strengths as well as the weaknesses of the Kuala Lumpur High Court (Family Court) in Malaysia. More importantly, the research paper lays out the recommendations as to whether the Family Court could be implemented in all states in Malaysia by referring to the practices of Family Courts in Singapore and Australia. The research is set out systematically. Firstly, it deals with the historical background, structure and jurisdiction of Kuala Lumpur High Court (Family Court) in Chapter Two. Secondly, in Chapter Three there are comparisons made between the Family Courts in Singapore and Australia. Thirdly, Chapter Four will highlights on the strengths and weaknesses of Kuala Lumpur High Court (Family Court) Malaysia. Finally, Chapter 5 sets out the conclusions, findings and recommendations for the research paper as a whole.